Safety and effectiveness of intravenous iron sucrose versus oral iron for correction of preoperative anemia in women with menorrhagia - N. Meghana, M.; M. Jitesh, S. (Scientific Journal of Medical Science, 2013)
To compare the safety and efficacy of iron sucrose over oral iron for the correction of preoperative anemia in women with menorrhagia. Methods: Women with mwnorrhagia having Hemoglobin (Hb) level less than 10 gm/dl and features of iron deficiency were included in the study. Women matching the inclusion and exclusion criteria, allocated to group A (IV iron sucrose) or group B (oral iron). IV iron sucrose was administered as 100 mg (2 ampoules) in 100 ml normal saline by slow IV infusion. The women in the group B received ferrous sulphate as oral iron in the dose of one tablet (200 mg salt) three times a day. Repeat laboratory estimations were done after four weeks. Results were analyzed by paired t test using SPSS 15 and Microsoft excel. Results: Before treatment, mean Hemoglobin level (mean ± SD) was similar in both groups (7.18 ± 1.18 gm/dl in group A and 7.18 ± 1.02 gm/dl in group B). After treatment, rise of Hb level was more in group A (10.70 ± 0.73 gm/dl) than group B (9.64 ± 0.70 gm/dl). After treatment, the desired Hb level of 10 gm/dl or more were achieved in 96% of women in group A while only in 56% of women in group B. Conclusion: Preoperative intravenous iron sucrose administration is more effective than oral iron and is as safe as oral iron therapy in the correction of preoperative anemia due to menorrhagia.